2022
DOI: 10.1177/08850666221086839
|View full text |Cite
|
Sign up to set email alerts
|

Cause of In-Hospital Death After Weaning from Venoarterial-Extracorporeal Membrane Oxygenation

Abstract: Purpose A survival gap between weaning from venoarterial-extracorporeal membrane oxygenation (VA-ECMO) and the hospital discharge has been consistently reported. The aim of this study is to investigate the clinical features of patients who underwent successful VA-ECMO decannulation at our institution and to identify the major contributors responsible for adverse outcomes. Methods We retrospectively reviewed all patients supported with VA-ECMO in our institution between January 2013 and June 2020. Only patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…The ECMO-related infection is a common complication, the rate of ECMO-related infections is associate with many factors, such as auxiliary time of VA-ECMO (22) and patients' quality of care (23). The infection rate seems higher in our study than ELSO interim guidelines (24), whereas, no patient was found by culture proven infection.…”
Section: Discussioncontrasting
confidence: 46%
“…The ECMO-related infection is a common complication, the rate of ECMO-related infections is associate with many factors, such as auxiliary time of VA-ECMO (22) and patients' quality of care (23). The infection rate seems higher in our study than ELSO interim guidelines (24), whereas, no patient was found by culture proven infection.…”
Section: Discussioncontrasting
confidence: 46%
“…This is consistent with previously reported infectious agents. 19 Therefore, when performing VA-ECMO surgery, catheter care, and strict aseptic procedures, especially cleaning and maintenance of the airway and central venous access, may be important measures to prevent VA-ECMOrelated hospital infections. 9,21,30 Neonates on ECMO have a higher incidence of mixed infections due to their immunocompromised status and the placement of multiple invasive catheters.…”
Section: Discussionmentioning
confidence: 99%
“…However, ECMO may increase the risk of ECMO-associated nosocomial infections because it can induce abnormal immune function in patients through pan-endothelial damage, leukocyte activation, and pro-inflammatory responses, as well as pharmacokinetic and pharmacodynamic changes in antimicrobial drugs. 19 Infection is one of the most common complications in ECMO patients, leading to increased morbidity and mortality. 20 The rate of hospital-acquired infections in ECMO neonates has been reported to be significantly higher than in non-ECMO neonates (13.8 vs. 8.8/1000 ICU admission days) and has serious consequences, leading to prolonged ECMO support time, duration of mechanical ventilation, duration of central venous catheterization and ICU stay.…”
Section: Discussionmentioning
confidence: 99%